Heterotic effects on fitness in a wild bird population - Merila, J; Sheldon, B; Griffith, S (2003)
The role of genetic variation in determining fitness in natural populations has been enigmatic for decades. Both theoretical and empirical work suggest that additive genetic contributions to fitness variation are small, whereas observations of inbreeding depression suggest that non-additive genetic contributions to fitness can sometimes be large. We analysed associations between genetic variability at a small number of microsatellite loci and fitness in a natural population of the collared flycatcher Ficedula albicollis, and related these to estimates of additive genetic contributions to the same traits. We found strong single-locus associations between an intra-locus measure of variability (d2) and variables related to fitness. These heterotic effects were sex-specific, being found only in males, and variation at this locus explained as much as 11% of the variance in male lifetime reproductive success. The size of the heterotic effect on a trait depended on how closely that trait was related to fitness, and there was a negative relationship between the size of the heterotic effect and the proportion of a trait's variance due to additive genetic variance. One possibility is that the heterosis results from introgression due to hybridization with the closely related pied flycatcher F. hypoleuca. Our results provide evidence that genetic contributions to fitness can be important in outbred populations.